2020
DOI: 10.1002/adem.202000622
|View full text |Cite
|
Sign up to set email alerts
|

Hot Deformation Characteristics and Dynamic Recrystallization Mechanisms of a Novel Nickel‐Based Superalloy

Abstract: The hot deformation characteristics of a novel nickel‐based superalloy is investigated via the isothermal compression test in temperature range of 1000–1150 °C and strain rate of 0.001–10 s−1 under the true strain of 0.8. The hot deformation characteristics of GH4065 alloy are studied here for the first time. Based on the flow stress data, it is observed the typical features of flow curves exhibit the occurrence of dynamic recrystallization (DRX) during the hot deformation process. The constitutive equation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…It suggested that the sub-grain merging and rotation becomes slight at the true strain of 0.5. This phenomenon demonstrates that the deformed grains transform into the dislocation-free DRX grains [28]. With the true strain further increasing from 0.5 to 0.7, it can be found that the point to origin misorientations obviously increases, and the point to point misorientations scarcely exceed 0.5 both along the G1 line and G2 line in Figure 4g, as shown in Figure 5g,h.…”
Section: Microstructure Evolutionmentioning
confidence: 76%
See 3 more Smart Citations
“…It suggested that the sub-grain merging and rotation becomes slight at the true strain of 0.5. This phenomenon demonstrates that the deformed grains transform into the dislocation-free DRX grains [28]. With the true strain further increasing from 0.5 to 0.7, it can be found that the point to origin misorientations obviously increases, and the point to point misorientations scarcely exceed 0.5 both along the G1 line and G2 line in Figure 4g, as shown in Figure 5g,h.…”
Section: Microstructure Evolutionmentioning
confidence: 76%
“…The similar evolution characteristic of the misorientation jumps is also shown in Figure 5a,b. This phenomenon indicates that different orientation bands exist in the deformed grains, resulting from different slip systems activated for coordinating the strain between the adjacent grains [28,36].With the true strain of 0.5, it is easily observed that the point to origin misorientations and the point to point misorientations obviously decreases, and scarcely exceed 0.3 • both along the E1 line and E2 line in Figure 4e, as shown in Figure 5e,f. It suggested that the sub-grain merging and rotation becomes slight at the true strain of 0.5.…”
Section: Microstructure Evolutionmentioning
confidence: 89%
See 2 more Smart Citations
“…[ 27 ] The dislocation density increased with strain until the critical strain point, and then, DRX was activated. [ 28 ] Finally, the flow stress was stable at a large strain, indicating that dynamic softening offset work hardening, leading to equilibrium. However, from the EP741NP alloy stress–strain curves, at low temperatures or high strain rates, dynamic equilibrium was not reached even at a maximum strain of 0.5, and this was mainly ascribed to incomplete DRX.…”
Section: Resultsmentioning
confidence: 99%